Organophosphate pesticide metabolite concentrations in urine during pregnancy and offspring attention-deficit hyperactivity disorder and autistic traits. (October 2019) - van den Dries, Michiel A.; Guxens, Mònica; Pronk, Anjoeka; Spaan, Suzanne; El Marroun, Hanan; Jusko, Todd A.; Longnecker, Matthew P.; Ferguson, Kelly K.; Tiemeier, Henning
Abstract: Background: Prenatal exposure to organophosphate (OP) pesticides has been associated with altered neuronal cell development and behavioral changes in animal offspring. However, the few studies investigating the association between prenatal OP pesticide exposure and neurodevelopmental outcomes such as Attention-Deficit Hyperactivity Disorder (ADHD) and autistic traits in children produced mixed findings. Objective: The objective of the present study was to examine whether maternal urinary concentrations of OP pesticide metabolites are associated with ADHD and autistic traits in children participating in the Generation R Study, a population-based birth cohort from Rotterdam, the Netherlands. Method: Maternal concentrations of 6 dialkylphosphates (DAPs) were measured using gas chromatography coupled with tandem mass spectrometry in urine samples collected at <18 weeks, 18‐25 weeks, and > 25 weeks of gestation in 784 mother-child pairs. DAP metabolite concentrations were expressed as molar concentrations divided by creatinine levels and log10 transformed. ADHD traits were measured at ages 3, 6, and 10 years using the Child Behavior Checklist (CBCL) ( n = 781) and autistic traits were measured at age 6 years using the Social Responsiveness Scale (SRS) ( n = 622). First, regression models were fit for the averaged prenatal exposure across pregnancy. Second, we investigated associations for each collection phase separately, and applied a mutually adjusted model in which the effect of prenatal DAP concentrations from each time period on ADHD and autistic traits were jointly estimated. All associations were adjusted for relevant confounders. Results: Median DAP metabolite concentration was 309 nmol/g creatinine at <18 weeks, 316 nmol/g creatinine at 18–25 weeks, and 308 nmol/g creatinine at >25 weeks of gestation. Overall, DAP metabolite concentrations were not associated with ADHD traits. For instance, a log10 increase in averaged total DAP concentrations across gestation was not associated with a lower ADHD score (-0.03 per SD 95 CI: −0.28 to 0.23). Similarly, no associations between maternal DAP concentrations and autistic traits were detected. Conclusions: In this study of maternal urinary DAP metabolite concentrations during pregnancy, we did not observe associations with ADHD and autistic traits in children. These are important null observations because of the relatively high background DAP concentrations across pregnancy, the relatively large sample size, and the 10-year follow-up of the offspring. Given the measurement error inherent in our OP pesticide exposure biomarkers, future studies using more urine samples are needed to accurately measure OP pesticide exposure over pregnancy in relation to ADHD and autistic traits. Highlights: We explored whether prenatal exposure to OP pesticides is associated with ADHD and autistic traits in children Maternal urinary concentrations of six DAP metabolites were measured during early, mid, and late pregnancy DAP metabolite concentrations in this study were 2-3 times higher compared with concentrations measured in most other studies Maternal DAP concentrations were not associated with ADHD and autistic traits in children.